Asphalt-based hard alloy anti-sticking coating, burning bearing device and application of asphalt-based hard alloy anti-sticking coating

By using asphalt-based cemented carbide anti-adhesive coatings, the problems of poor stability and insufficient adhesion of existing anti-adhesive coatings are solved, and the stability and number of times of use of anti-adhesive coatings during cemented carbide sintering are improved.

CN119709013APending Publication Date: 2025-03-28XIAMEN TUNGSTEN CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411885722.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing anti-adhesive coatings for cemented carbide sintering have poor stability and insufficient adhesion to graphite plates, resulting in a decrease in the quality of cemented carbide and a decrease in the number of times of use of burning devices.

Method used

Asphalt-based cemented carbide anti-adhesive coating is used, which contains graphite powder, carbon black particles, inorganic particles, emulsified asphalt, thickener and dispersant. The anti-adhesive coating is formed through drying and heat treatment to enhance adhesion with the graphite plate.

Benefits of technology

It improves the stability of the anti-stick coating and extends the number of times of use of the anti-stick coating through strong adhesion, reducing production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of coatings, and particularly relates to an asphalt-based hard alloy anti-sticking coating, a burning bearing device, a preparation method of the asphalt-based hard alloy anti-sticking coating, the burning bearing device and application of the burning bearing device. The asphalt-based hard alloy anti-sticking coating contains graphite powder, carbon black particles, inorganic particles, emulsified asphalt, a thickening agent and a dispersing agent. The asphalt-based hard alloy anti-sticking coating provided by the invention has good stability, and an anti-sticking coating layer formed by the asphalt-based hard alloy anti-sticking coating has strong adhesive force with a graphite plate, so that the asphalt-based hard alloy anti-sticking coating has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coatings, and in particular relates to an asphalt-based hard alloy anti-sticking coating and a burning device and applications thereof. Background Art

[0002] Cemented carbide is an alloy composite material formed by powder metallurgy sintering with refractory metal carbides (such as tungsten carbide) as the hard phase and metal binders (such as cobalt, nickel, iron) as the bonding phase. The cobalt seepage during the sintering process of cemented carbide will cause the alloy sample to stick to the bearing surface of the sintering device (usually a graphite plate), commonly known as "sticking plate". "Sticking plate" will seriously affect the quality of cemented carbide and reduce the number of times the sintering device is used. Among them, high-cobalt cemented carbide is more prone to "sticking plate". In view of this, during the sintering process of cemented carbide, anti-stick coatings need to be used to isolate the cemented carbide and the bearing surface to ensure that there is no reaction with the bearing surface during the sintering process to cause degradation of cemented carbide performance and "sticking plate" phenomenon.

[0003] The traditional anti-stick coating used in cemented carbide sintering mainly contains isolation filler (such as graphite powder, carbon black particles, inorganic particles, etc.) and various additives and solvents, etc., and is mixed. When sintering cemented carbide, the anti-stick coating is applied to the load-bearing surface, and the anti-stick coating is formed after the coating is dried. However, due to the large difference in the specific gravity of carbon materials, especially graphite powder and inorganic particles, the coating will be easily separated during storage, and it is difficult to form a stable system, which causes the material to be easy to settle, affecting the uniformity of construction and smearing. In addition, the anti-stick coating formed by traditional anti-stick coating often cracks, falls off, and powderizes after sintering to reduce the adhesion of the anti-stick coating and the load-bearing surface, which causes the anti-stick coating to be rarely reused, and the anti-stick coating needs to be re-applied before each use, which greatly increases the production cost. And traditional anti-stick coatings often need to increase the amount of graphite powder in order to enhance the adhesion strength on the load-bearing surface, but too much graphite powder can weaken the isolation effect of the anti-stick coating. Summary of the invention

[0004] The first purpose of the present invention is to overcome the defects of the existing anti-stick coating used for cemented carbide sintering, which has poor stability and poor adhesion to graphite plates, and to provide a new asphalt-based cemented carbide anti-stick coating, which has good stability and the anti-stick coating formed by the asphalt-based cemented carbide anti-stick coating has strong adhesion to the graphite plate.

[0005] The second object of the present invention is to provide the application of the above-mentioned asphalt-based cemented carbide anti-stick coating in cemented carbide sintering.

[0006] The third object of the present invention is to provide a sintering device, the bearing surface of which has an anti-stick coating obtained by applying the above-mentioned anti-stick coating in the sintering of cemented carbide.

[0007] The fourth object of the present invention is to provide application of the above-mentioned sintering device in cemented carbide sintering.

[0008] Specifically, the asphalt-based cemented carbide anti-stick coating provided by the present invention contains graphite powder, carbon black particles, inorganic particles, emulsified asphalt, a thickener and a dispersant.

[0009] The application process of the anti-stick coating provided by the present invention in cemented carbide sintering includes coating the asphalt-based cemented carbide anti-stick coating on the bearing surface of the sintering device, drying after coating to volatilize the solvent, and then heat treating in an inert atmosphere to carbonize the asphalt to obtain the anti-stick coating.

[0010] The asphalt-based hard alloy anti-stick coating provided by the invention not only has good stability, but also the anti-stick coating formed by the asphalt-based hard alloy anti-stick coating has strong adhesion with the graphite plate. The reasons are speculated to be: on the one hand, graphite powder is naturally hydrophobic and is difficult to disperse evenly in the coating. The use of graphite powder, carbon black particles and inorganic particles as insulating fillers can reduce the amount of graphite powder used and improve the stability of the coating. At the same time, the introduction of emulsified asphalt can stably disperse the insulating filler in the solution and improve the stability of the coating. On the other hand, the molecular structure of asphalt contains multiple active groups, which can interact with the polar groups on the graphite particles on the surface of the graphite plate to form physical adsorption. In addition, asphalt has good wettability and surface tension, and can quickly cover and adsorb on the surface of graphite particles to form a close contact to enhance the bonding effect. At the same time, asphalt can penetrate into the tiny pores and cracks of graphite during the cooling and solidification process to form a strong mechanical bite. This penetration and solidification process enhances the bonding force between asphalt and graphite plate. In the specific use process, the anti-stick coating is applied to the graphite plate and dried. As the solvent evaporates, the internal components of the anti-stick coating are redistributed, and the asphalt and the insulating filler are squeezed and wrapped around each other to form a solid anti-stick coating. DETAILED DESCRIPTION

[0011] The asphalt-based cemented carbide anti-stick coating provided by the present invention contains graphite powder, carbon black particles, inorganic particles, emulsified asphalt, a thickener and a dispersant. The asphalt-based cemented carbide anti-stick coating usually also contains water, and the amount of water is preferably such that the solid content of the asphalt-based cemented carbide anti-stick coating is 30 to 60wt%, such as 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt% or any value therebetween.

[0012] In a preferred embodiment, based on the total weight of the asphalt-based cemented carbide anti-stick coating, the content of the graphite powder is 1-10wt%, such as 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt% or any value therebetween; the content of the carbon black particles is 1-25wt%, such as 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 25wt% or any value therebetween; the content of the inorganic particles is 1-30wt%, such as 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 25wt% or any value therebetween. t%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt% or any value therebetween; the content of the emulsified asphalt is 1-20%, such as 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt% or any value therebetween; the content of the thickener is 0.5-10%, such as 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt% or any value therebetween; the content of the dispersant is 0.5-15%, such as 0.5wt%, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 15wt% or any value therebetween.

[0013] In the present invention, the graphite powder may be unmodified graphite powder, modified graphite powder, or a mixture of the two. The graphite powder may be at least one of natural graphite powder, flake graphite powder, and expanded graphite powder. In addition, the particle size of the graphite powder is preferably 200 to 15000 mesh, such as 200 mesh, 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 2000 mesh, 3000 mesh, 4000 mesh, 6000 mesh, 8000 mesh, 10000 mesh, 12000 mesh, 14000 mesh, 15000 mesh, or any value therebetween.

[0014] In the present invention, the particle size of the carbon black particles is preferably 10 nm to 200 nm, such as 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm or any value therebetween.

[0015] In the present invention, the inorganic particles may be at least one of metal oxide particles, metal carbides, metal nitrides, silicate particles and carbonate particles. The metal oxide particles may be at least one of aluminum oxide, zirconium oxide, silicon oxide and rare earth oxides. The rare earth element in the rare earth oxide may be 15 lanthanide elements with atomic numbers of 57 to 71 in the periodic table and scandium (Sc) and yttrium (Y) with similar chemical properties to the lanthanide elements. Specific examples of the lanthanide elements include, but are not limited to, at least one of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu). Accordingly, specific examples of the rare earth oxide include, but are not limited to, at least one of lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, samarium oxide, europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, erbium oxide, thulium oxide, ytterbium oxide, lutetium oxide, scandium oxide, and yttrium oxide. The metal carbide may be at least one of zirconium carbide, silicon carbide, etc. The metal nitride may be at least one of zirconium nitride, silicon nitride, etc. The silicate particles may be at least one of quartz sand, mica particles, talc particles, feldspar particles, and montmorillonite particles. The carbonate particles may be at least one of calcium carbonate, magnesium carbonate, calcite, dolomite, and siderite. From the perspective of the availability of raw materials, the inorganic particles are particularly preferably at least one of aluminum oxide, zirconium oxide, zirconium carbide, silicon oxide, silicon nitride, silicon carbide, and rare earth oxides. In addition, the particle size of the inorganic particles is preferably 0.1 μm to 10 μm, specifically 0.1 μm, 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, etc.

[0016] In the present invention, the term "emulsified asphalt" refers to an oil-in-water or water-in-oil asphalt emulsion formed by asphalt being dispersed in an emulsifier in a state of tiny droplets. The emulsified asphalt can be stably suspended and dispersed in the anti-stick coating, and its use as a modifier can effectively improve the stability of the anti-stick coating. At the same time, the strong penetration and bite ability of the asphalt itself and the polar groups contained therein can effectively improve the adhesion between the anti-stick coating and the graphite plate. The solid content of the asphalt in the emulsified asphalt is preferably 20 to 50wt%, such as 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or any value therebetween. In addition, the emulsifier contained in the emulsified asphalt can be selected from at least one of peregrin, alkyl polyoxyethylene ether, cyclopentane acid aluminum soap, saponin, sodium dodecyl sulfonate, phospholipids, C16 to C20 aliphatic hydrocarbon substituted ethylene or propylene diamine, etc.

[0017] In the present invention, the thickener may be any existing substance that is conducive to the suspension of graphite powder, carbon black particles and inorganic particles in the anti-stick coating, for example, it may be selected from at least one of an inorganic thickener, a cellulose thickener, an ether thickener, a polyacrylic thickener, an ester thickener and a colloid thickener. Specific examples of the inorganic thickener include, but are not limited to, at least one of halloysite, attapulgite, sepiolite, montmorillonite, bentonite, carbon nanotubes, silicon carbide, etc. Specific examples of the cellulose thickener include, but are not limited to, at least one of methyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose and hydroxyethyl cellulose. Specific examples of the ether thickener include, but are not limited to, at least one of cetyl alcohol polyoxyethylene (3) ether, isocetyl alcohol polyoxyethylene (10) ether, lauryl alcohol polyoxyethylene (3) ether, lauryl alcohol polyoxyethylene (10) ether and polyoxyethylene polyoxypropylene ether. The polyacrylic acid thickener is generally polymerized from three or more monomers, wherein the first monomer is generally a carboxylic acid monomer, for example, it can be selected from at least one of acrylic acid, methacrylic acid, maleic acid, maleic anhydride, etc.; the second monomer is generally an acrylate or styrene; the third monomer is generally a cross-linking monomer, for example, it can be selected from at least one of N, N-methylenebisacrylamide, dibutyl acrylate and dipropylene phthalate, etc. Specific examples of the colloid thickener include, but are not limited to: at least one of carrageenan, gelatin, xanthan gum, pectin, alginate, etc. The thickener is preferably a one-dimensional inorganic thickener, because compared with other types of thickeners, the one-dimensional structure of such thickeners can be cross-linked and entangled with each other in the anti-stick coating, enhancing the toughness of the coating, and at the same time, such thickeners are more conducive to the matching of the expansion coefficient between the graphite plate and the anti-stick coating, so that the anti-stick coating has a stronger binding force with the graphite plate. The term "one-dimensional inorganic thickener" refers to an inorganic material thickener in which electrons move freely only in one nanoscale direction. The aspect ratio of the one-dimensional inorganic thickener is preferably 50 to 1000, such as 50, 80, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000 or any value therebetween. The one-dimensional inorganic thickener is preferably selected from at least one of natural one-dimensional minerals, carbon nanotubes and one-dimensional silicon carbide. The natural one-dimensional mineral preferably does not contain alkali metal elements and / or alkaline earth metal elements. The alkali metal elements include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs) and francium (Fr). The alkaline earth metal elements include beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba) and radium (Ra). In order to facilitate the matching of the expansion coefficients between the graphite plate and the insulating layer, the one-dimensional inorganic thickener is preferably at least one selected from the group consisting of halloysite, attapulgite, sepiolite, montmorillonite and bentonite.

[0018] In the present invention, the dispersant can be any existing inert liquid substance that is conducive to the uniform dispersion of the asphalt-based cemented carbide anti-stick coating, such as at least one of polyethylene oxide, polyoxyethylene sorbitan fatty acid ester and sorbitan fatty acid ester. Specific examples of the polyethylene oxide include but are not limited to: at least one of PEO-200, PEO-400, PEO-600, PEO-800, PEO-1000, PEO-2000, PEO-4000, etc. Specific examples of the polyoxyethylene sorbitan fatty acid ester include but are not limited to: at least one of Tween 20, Tween 40, Tween 60, Tween 80, etc. Specific examples of the sorbitan fatty acid ester include but are not limited to: at least one of Span 20, Span 40, Span 60, Span 80, etc.

[0019] The application process of the asphalt-based cemented carbide anti-stick coating provided by the present invention in cemented carbide sintering includes coating the asphalt-based cemented carbide anti-stick coating on the bearing surface of the sintering device, drying after coating to volatilize the solvent, and then heat-treating the obtained primary anti-stick coating layer under an inert atmosphere to carbonize the asphalt to obtain an anti-stick coating.

[0020] In the application process of the above-mentioned anti-stick coating in the sintering of cemented carbide, the drying conditions preferably include a temperature of 35°C to 200°C, such as 35°C, 40°C, 45°C, 50°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C or any value therebetween; a time of 1h to 10h, such as 1h, 2h, 4h, 6h, 8h, 10h or any value therebetween. The inventors of the present invention have found through in-depth research that when the drying temperature is too high (higher than 100°C), the anti-stick coating formed will be used for multiple sintering of cemented carbide and will show more serious carburization. It is speculated that the reason may be that: too high a drying temperature will lead to enhanced gas fluidity, softening the anti-stick coating, thereby causing part of the graphite powder to migrate upward. During the repeated sintering process, part of the graphite powder is exposed and contacts with the cemented carbide, and then chemically reacts with the elements in the cemented carbide to cause the occurrence of carburization. In view of this, the drying temperature is preferably controlled at 35°C to 100°C, such as 35°C, 40°C, 45°C, 50°C, 80°C, 100°C or any value therebetween. Accordingly, the drying time is preferably controlled at 2h to 6h, such as 2h, 3h, 4h, 5h, 6h or any value therebetween. In addition, in order to facilitate the rapid volatilization of the solvent, the drying is carried out under blast conditions.

[0021] In the application process of the above-mentioned anti-stick coating in the sintering of cemented carbide, the heat treatment conditions preferably include a temperature of 500°C to 1500°C, such as 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or any value therebetween; the time is 1h to 10h, such as 1h, 2h, 4h, 6h, 8h, 10h or any value therebetween. The inventors of the present invention have found through in-depth research that when the heat treatment temperature is higher than 1300°C, the anti-stick coating formed will show slight carburization after multiple sintering of cemented carbide. It is speculated that the reason may be that: too high a heat treatment temperature will cause the coating and the graphite plate to shrink inconsistently, and there will be residual stress. During repeated sintering, the coating strength is reduced and the insulation effect is weakened, so that the cemented carbide sample and the underlying graphite plate may come into contact, thereby causing carburization. In view of this, the temperature of the heat treatment should preferably be controlled at 500°C to 1300°C, such as 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C or any value therebetween. Accordingly, the drying time should preferably be controlled at 2h to 6h, such as 2h, 3h, 4h, 5h, 6h or any value therebetween. The heat treatment is carried out in an inert atmosphere, which can generally be at least one of nitrogen, helium and argon.

[0022] The bearing surface of the sintering device provided by the present invention has an anti-stick coating obtained by applying the above anti-stick coating in the sintering of cemented carbide.

[0023] In addition, the present invention also provides application of the above-mentioned sintering device in sintering of cemented carbide.

[0024] The present invention will be described in detail below through examples.

[0025] In the following examples and comparative examples, emulsified asphalt was purchased from China Railway Weiye Waterproof Material Technology Co., Ltd., with a grade of 8.22 cold base oil and an asphalt content of 50wt%; epoxy asphalt was purchased from China Railway Weiye Waterproof Material Technology Co., Ltd., with a grade of WY epoxy asphalt; liquid asphalt was purchased from Hebei Hankai Energy Technology Development Co., Ltd., with a grade of Hankai G001; asphalt particles were purchased from Hebei Hankai Energy Technology Development Co., Ltd., with a grade of HK-9; graphite powder was purchased from Shanghai Jixiang Industrial Co., Ltd., with a particle size of 3000 mesh to 8000 mesh and a particle size D90 of 5600nm; carbon black particles were purchased from Henan Ruibo Chemical Co., Ltd., with a particle size of 80nm to 110nm and a particle size D90 of 100nm; the particle size of the alumina powder was 4μm to 5μm and the particle size D90 was 4.6μm; the particle size of the zirconium oxide powder was 1μm to 2μm and the particle size D90 was 1 .8μm; the particle size of lanthanum oxide powder is 1μm~3μm and the particle size D90 is 2.1μm; attapulgite powder has a one-dimensional structure and is purchased from Mingguang Hengding Attapulgite Co., Ltd., with a length of 1000nm~3000nm and an average length of 1600nm, an aspect ratio of (10~30):1 and an average aspect ratio of 14.2:1; halloysite powder has a one-dimensional structure and is purchased from Lingshou Qianfu Mineral Products Processing Plant, with a length of 3000nm~5000nm and an average length of 4100nm, an aspect ratio of (30~50):1 and an average aspect ratio of 38:1; sepiolite powder has a one-dimensional structure and is purchased from Aladdin Biochemical Technology Co., Ltd., with a length of 10000nm~20000nm and an average length of 18500nm, an aspect ratio of (200~400):1 and an average aspect ratio of 320:1.

[0026] Example 1

[0027] Step 1: By weight, 1 part of graphite powder, 2 parts of carbon black, 5 parts of alumina powder, 1 part of emulsified asphalt, 1.5 parts of attapulgite powder, 1 part of 10% by mass Tween 80 and 16 parts of water are stirred and mixed at 2000 r / min for 12 hours to obtain an asphalt-based cemented carbide anti-stick coating;

[0028] Step 2: Apply the asphalt-based cemented carbide anti-stick coating on the surface of the graphite plate and dry it at 60°C for 2 hours to obtain a primary anti-stick coating. Heat treat the graphite plate with the primary anti-stick coating at 800°C for 6 hours in a nitrogen atmosphere to further carbonize the asphalt to form an anti-stick coating layer.

[0029] Example 2

[0030] Step 1: By weight, 2 parts of graphite powder, 2 parts of carbon black, 8 parts of zirconium oxide powder, 2 parts of emulsified asphalt, 3 parts of halloysite powder, 1 part of PEO 2000 and 16 parts of water were stirred and mixed at 2000 r / min for 12 hours to obtain an asphalt-based cemented carbide anti-stick coating;

[0031] Step 2: Apply the asphalt-based cemented carbide anti-stick coating on the surface of the graphite plate and dry it at 35°C for 6 hours to obtain a primary anti-stick coating. The graphite plate with the primary anti-stick coating is heat treated at 1300°C for 2 hours in a nitrogen atmosphere to further carbonize the asphalt to form an anti-stick coating layer.

[0032] Example 3

[0033] Step 1: By weight, 3 parts of graphite powder, 3 parts of carbon black, 6 parts of lanthanum oxide powder, 5 parts of emulsified asphalt, 2 parts of sepiolite powder, 1 part of 10% by mass Span 60 and 16 parts of water were stirred and mixed at 2000 r / min for 12 hours to obtain an asphalt-based cemented carbide anti-stick coating;

[0034] Step 2: Apply the asphalt-based hard alloy anti-stick coating on the surface of the graphite plate and dry it at 100°C for 2 hours to obtain a primary anti-stick coating. Heat treat the graphite plate with the primary anti-stick coating at 500°C for 6 hours in a nitrogen atmosphere to further carbonize the asphalt to form an anti-stick coating layer.

[0035] Example 4

[0036] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that the attapulgite powder was replaced by the same weight portion of methyl cellulose. The other conditions were the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0037] Example 5

[0038] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 1 and an anti-stick coating was formed on a graphite plate, except that the drying temperature was increased to 180°C. The other conditions were the same as in Example 1, and an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto were obtained.

[0039] Example 6

[0040] An asphalt-based cemented carbide anti-stick coating is prepared according to the method of Example 1 and is used to form an anti-stick coating on a graphite plate. The difference is that the heat treatment temperature is increased to 1500°C, and the other conditions are the same as in Example 1, to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0041] Example 7

[0042] An asphalt-based cemented carbide anti-stick coating is prepared according to the method of Example 1 and is used to form an anti-stick coating on a graphite plate. The difference is that the heat treatment temperature is increased to 1700°C, and the other conditions are the same as in Example 1, to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0043] Example 8

[0044] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that the amount of emulsified asphalt was increased to 5 parts. The other conditions were the same as in Example 1, and an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto were obtained.

[0045] Example 9

[0046] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that the amount of emulsified asphalt was increased to 8 parts. The other conditions were the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0047] Example 10

[0048] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that the amount of emulsified asphalt was reduced to 0.1 parts. The other conditions were the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0049] Comparative Example 1

[0050] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 4 and an anti-stick coating was formed on a graphite plate, except that emulsified asphalt was not added. The other conditions were the same as in Example 4, and an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto were obtained.

[0051] Comparative Example 2

[0052] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Comparative Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that the amount of graphite powder was increased to 3 parts, and the other conditions were the same as those of Comparative Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0053] Comparative Example 3

[0054] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Comparative Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that methyl cellulose was replaced by attapulgite powder in the same weight portion, and the other conditions were the same as those of Comparative Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0055] Comparative Example 4

[0056] An asphalt-based cemented carbide anti-stick coating is prepared according to the method of Example 1 and is used to form an anti-stick coating on a graphite plate. The difference is that the emulsified asphalt is replaced by the same weight portion of epoxy asphalt. The other conditions are the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0057] Comparative Example 5

[0058] An asphalt-based cemented carbide anti-stick coating is prepared according to the method of Example 1 and is used to form an anti-stick coating on a graphite plate. The difference is that the emulsified asphalt is replaced by the same weight portion of liquid asphalt. The other conditions are the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0059] Comparative Example 6

[0060] An asphalt-based cemented carbide anti-stick coating is prepared according to the method of Example 1 and is used to form an anti-stick coating on a graphite plate. The difference is that the emulsified asphalt is replaced by asphalt particles of the same weight. The other conditions are the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0061] Comparative Example 7

[0062] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that the drying step was omitted: drying was performed at 60°C for 2 hours, and the other conditions were the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0063] Comparative Example 8

[0064] An asphalt-based cemented carbide anti-stick coating was prepared according to the method of Example 1 and an anti-stick coating was formed on a graphite plate. The difference was that the heat treatment step was omitted: the graphite plate with the primary anti-stick coating was heat treated at 800°C for 6 hours in a nitrogen atmosphere, and the other conditions were the same as in Example 1 to obtain an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating.

[0065] Comparative Example 9

[0066] An asphalt-based cemented carbide anti-stick coating is prepared according to the method of Example 1 and is used to form an anti-stick coating on a graphite plate. The difference is that the heat treatment temperature is reduced to 400°C (not reaching the carbonization temperature of asphalt), and the remaining conditions are the same as in Example 1, thereby obtaining an asphalt-based cemented carbide anti-stick coating and a graphite plate with an anti-stick coating attached thereto.

[0067] Test Case

[0068] (1) Stability: The anti-stick coatings obtained in the above embodiments and comparative examples were left to stand for 24 hours to observe whether there was sedimentation and / or phase separation to determine the stability of the anti-stick coatings. If there was no sedimentation and no phase separation, it means that the anti-stick coating is stable. On the contrary, if there was sedimentation and / or phase separation, it means that the stability of the anti-stick coating itself was poor and no subsequent tests were performed. The results are shown in Table 1.

[0069] (2) Isolation effect: The graphite plates attached with the anti-stick coating obtained in the above embodiments and comparative examples are placed in a sintering furnace respectively, and the cemented carbide is sintered under the same conditions. The isolation effect of the coating and the bonding force between the coating and the graphite plate are judged by the maximum number of times the anti-stick coating attached to the graphite plate is used, and the cause of failure of the anti-stick coating (sticking to the plate, carburization or falling off) is explored when the maximum number of times used is +1. Among them, the maximum number of times the anti-stick coating is used refers to the maximum number of times that there is no sticking to the plate, carburization, powdering at the edge, cracking, falling off and powdering in the center of the graphite plate. If at least one of sticking to the plate, carburization, powdering at the edge, cracking, falling off and powdering in the center of the graphite plate occurs, it means that the coating no longer meets the use requirements. The results are shown in Table 1.

[0070] Table 1

[0071] serial number stability Maximum number of uses Whether to stick the board Whether carburizing Whether it falls off Example 1 No precipitation and no phase separation 9 times no no Partial shedding Example 2 No precipitation and no phase separation 9 times no no Partial shedding Example 3 No precipitation and no phase separation 8 times no Slight carburization Partial shedding Example 4 No precipitation and no phase separation 6 times no Slight carburization no Example 5 No precipitation and no phase separation 5 times no Severe carburization no Example 6 No precipitation and no phase separation 7 times no Slight carburization no Example 7 No precipitation and no phase separation 5 times no Slight carburization Large area shedding Example 8 No precipitation and no phase separation 10 times no Slight carburization no Example 9 No precipitation and no phase separation 6 times no Slight carburization Partial shedding Example 10 No precipitation and no phase separation 5 times no Slight carburization Large area shedding Comparative Example 1 No precipitation and no phase separation 1 time yes Slight carburization Large area shedding Comparative Example 2 No precipitation and no phase separation 4 times no carburization Partial shedding Comparative Example 3 No precipitation and no phase separation 3 times no Slight carburization Partial shedding Comparative Example 4 Obvious phase separation / / / / Comparative Example 5 Obvious phase separation / / / / Comparative Example 6 Obvious phase separation / / / / Comparative Example 7 No precipitation and no phase separation 3 times no carburization no Comparative Example 8 No precipitation and no phase separation 0 times yes Severe carburization no Comparative Example 9 No precipitation and no phase separation 3 times no Severe carburization no

[0072] From the results in Table 1, it can be seen that the anti-stick coating provided by the present invention has no precipitation and phase separation after being left to stand for 24 hours, indicating that it has excellent stability. In addition, the maximum number of uses of the graphite plate with the anti-stick coating provided by the present invention during the sintering process of the cemented carbide is large, which can be explained that the anti-stick coating provided by the present invention has excellent isolation effect and the anti-stick coating formed by it has strong adhesion with the graphite plate, and has broad application prospects.

[0073] Furthermore, the study shows that the anti-stick coating obtained in Example 1 and Example 2 was repeatedly sintered for 9 times without sticking to the plate, and the cemented carbide did not appear carburization after sintering, but after the 10th sintering, it was found that the anti-stick coating at the edge of the graphite plate had local shedding, but no powdering was found, which shows that the anti-stick coating constructed in Example 1 has strong mechanical strength. The anti-stick coating obtained in Example 3 was repeatedly sintered for 8 times without sticking to the plate, and the cemented carbide did not appear carburization after sintering, but after the 9th sintering, it was found that the graphite plate had slight carburization and the anti-stick coating at the edge had local shedding, and no powdering was found. The anti-stick coating obtained in Example 4 was repeatedly sintered for 6 times without sticking to the plate, but from the 7th time, the cemented carbide appeared slight carburization after sintering, but there was no cracking or powdering in the center of the graphite plate, which shows that the repeated shrinkage and expansion of the coating after 7 sinterings and the bonding force of the graphite plate are reduced. The anti-stick coating obtained in Example 5 was repeatedly sintered for 5 times, and the sticking plate appeared, and no anti-sticking coating was found to fall off, but the cemented carbide was severely carburized after the 6th sintering. Example 6 The heat treatment temperature was increased to 1500 ° C, and the cemented carbide showed slight carburization after the 8th sintering. Example 7 The heat treatment temperature was increased to 1700 ° C, and the cemented carbide showed slight carburization after the 6th sintering, and the graphite plate fell off in a large area. Example 8 Increase the amount of asphalt to construct the anti-stick coating, and the anti-sticking coating was repeatedly sintered for 10 times without sticking, carburization, and powdering. This shows that appropriately increasing the amount of asphalt binder can enhance the bonding force between the coating and the graphite plate, and the mechanical strength of the coating is also enhanced. Example 9 Increase the amount of asphalt to above the preferred range, and the repeated sintering 6 times did not cause sticking, carburization, and powdering, but after the 7th sintering, it was found that the graphite plate was slightly carburized and the anti-sticking coating at the edge fell off locally, and no powdering was found. In Example 10, the amount of asphalt was reduced to below the preferred range, and no sticking, carburization, or pulverization occurred after repeated sintering for 5 times. However, after the sixth sintering, it was found that the graphite plate was slightly carburized and the anti-stick coating at the edge fell off over a large area.

[0074] In addition, the conventional anti-stick coating constructed in Comparative Example 1 showed the phenomenon of coating powderization after the second sintering, and some cemented carbide samples had sticky plates. Comparative Example 2 increased the amount of graphite powder on the basis of Comparative Example 1, and the graphite plate showed a large range of powderization after repeated sintering for 5 times, but no sticky plates were seen. The conventional anti-stick coating constructed in Comparative Example 3 did not show sticky plates after sintering for 4 times, but the coating partially fell off at the edge of the graphite plate after the 4th sintering, without powderization. From the sintering test results of Comparative Examples 1, 2 and 3, it can be seen that increasing the content of graphite powder can also enhance the bonding force between the coating and the graphite plate, but compared with Examples 1 and 2, the adhesion strength between the anti-stick coating and the graphite plate is still relatively weak, and the repeated use of the anti-stick coating cannot be achieved. The anti-stick coatings obtained in Comparative Examples 4, 5 and 6 showed obvious phase separation and precipitation after standing for 24 hours, which shows that these coatings are unstable. At the same time, a large number of particles appeared on the surface of the anti-stick coating formed by these anti-stick coatings. This may be because the selected liquid asphalt, epoxy asphalt and asphalt particles cannot be evenly dispersed in the water system, resulting in asphalt agglomeration. This part of the agglomerated asphalt forms carbon particles after high-temperature heat treatment. Comparative Examples 7 and 8 do not include drying or heat treatment during the formation of the anti-stick coating, which will reduce the maximum number of uses and make the carburization phenomenon more obvious. When the heat treatment temperature of Comparative Example 9 is lower than the asphalt carbonization temperature, a large amount of asphalt is not carbonized, resulting in aggravated carburization and a significant decrease in the number of uses.

[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. An asphalt-based hard alloy anti-stick coating, characterized in that: The asphalt-based hard alloy anti-stick coating contains graphite powder, carbon black particles, inorganic particles, emulsified asphalt, a thickener and a dispersant.

2. The asphalt-based cemented carbide anti-stick coating according to claim 1, characterized in that: Based on the total weight of the asphalt-based cemented carbide anti-stick coating, the content of the graphite powder is 1 to 10wt%, the content of the carbon black particles is 1 to 25wt%, the content of the inorganic particles is 1 to 30wt%, the content of the emulsified asphalt is 1 to 20%, the content of the thickener is 0.5 to 10%, and the content of the dispersant is 0.5 to 15%.

3. The asphalt-based cemented carbide anti-stick coating according to claim 1, characterized in that: The particle size of the graphite powder is 200 mesh to 15000 mesh; the particle size of the carbon black particles is 10nm to 200nm; the particle size of the inorganic particles is 0.1μm to 10μm; Preferably, the inorganic particles are selected from at least one of aluminum oxide, zirconium oxide, zirconium carbide, silicon oxide, silicon nitride, silicon carbide and rare earth oxides.

4. The asphalt-based cemented carbide anti-stick coating according to claim 1, characterized in that: The solid content of the asphalt in the emulsified asphalt is 20 to 50 wt%.

5. The asphalt-based cemented carbide anti-stick coating according to claim 1, characterized in that: The thickener is selected from at least one of an inorganic thickener, a cellulose thickener, an ether thickener, a polyacrylic acid thickener, an ester thickener and a colloid thickener; Preferably, the thickener is a one-dimensional inorganic thickener; Preferably, the aspect ratio of the one-dimensional inorganic thickener is 50 to 1000; Preferably, the one-dimensional inorganic thickener is selected from at least one of natural one-dimensional minerals, carbon nanotubes and one-dimensional silicon carbide.

6. The asphalt-based cemented carbide anti-stick coating according to claim 1, characterized in that: The dispersant is selected from at least one of polyethylene oxide, polyoxyethylene sorbitan fatty acid ester and sorbitan fatty acid ester.

7. Application of an anti-stick coating in cemented carbide sintering, wherein the anti-stick coating is selected from the asphalt-based cemented carbide anti-stick coating according to any one of claims 1 to 6, characterized in that: The application process includes coating the bearing surface of the firing device with an asphalt-based hard alloy anti-stick coating, drying the coating to volatilize the solvent, and then heat-treating the asphalt in an inert atmosphere to carbonize the asphalt to obtain an anti-stick coating.

8. The use of the anti-sticking coating according to claim 7 in cemented carbide sintering, characterized in that: The drying conditions include a temperature of 35°C to 200°C, preferably 35°C to 100°C; a time of 1h to 10h, preferably 2h to 6h; The heat treatment conditions include a temperature of 500°C to 1500°C, preferably 500°C to 1300°C; and a time of 1h to 10h, preferably 2h to 6h.

9. A burning device, characterized in that: The bearing surface of the sintering device has an anti-stick coating obtained by using the anti-stick coating according to claim 7 or 8 in the sintering of cemented carbide.

10. Use of the sintering device according to claim 9 in sintering of cemented carbide.